Taxonomic revision of the genus Brounopsis Blair (Coleoptera: Cerambycidae: Cerambycinae) with description of four new species - Wang, Qiao; Lu, Wen (Zootaxa, 2013)
The longicorn beetle genus Brounopsis Blair, 1937, is revised. A diagnosis of Brounopsis and a key to all five species of the genus are given. One previously known species, B. hudsoni Blair, 1937, is redescribed, and four species described as new: B. concolora sp. nov., B. nigrifacta sp. nov., B. deitzi sp. nov. and B. gourlayi sp. nov. Dorsal views of each species are provided as photographs. The genus occurs exclusively in the South Island of New Zealand and is associated with Cassinia spp. (Asteraceae).